Lymphocytic hypophysitis masquerading as transient secondary hyperadrenalism followed by panhypopituitarism (Indian Journal of Case Reports, 2019)
Lymphocytic hypophysitis (LH) is a rare inflammatory disease of the pituitary gland. This condition strikingly shows female preponderance and commonly affects women during pregnancy or in the post-partum period. It’s a clinical presentation and radiological features may mimic pituitary adenoma. Though its treatment modality is uncertain steroid remains the 1st option for treatment. Here, we report an unusual case of LHin a 21-year-old female patient where initially, the patient presented with hyperadrenalism and secondary hyperthyroidism followed by pan-hypopituitarism (Addisonian crisis) which is attributed to initial autoimmune destruction of the gland followed by subsequent fibrosis. Thus, it is a rare case report which exquisitely explains this rare presentation and such cases should be investigated thoroughly since there are many differential and response to steroids is remarkable.